2018
DOI: 10.1007/s10637-018-0611-z
|View full text |Cite
|
Sign up to set email alerts
|

Discovering simple phenylboronic acid and benzoxaborole derivatives for experimental oncology – phase cycle-specific inducers of apoptosis in A2780 ovarian cancer cells

Abstract: Objective The aim of the study was to evaluate the antiproliferative potential of simple phenylboronic acid and benzoxaborole derivatives as well as to provide preliminary insight into their mode of action in cancer cells in vitro. Methods The antiproliferative activity was assessed in five diverse cancer cell lines via the SRB method (sulforhodamine B) or MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) method after 72 h of treatment. Further studies of the mechanism of action consisted of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…S2-4 †) also exhibited clear cell outlines with rounded shapes (mean roundness factor, RF: 0.77 ± 0.14; where RF = 1 implies perfect circularity), large cell nuclei, and overall area ranged between 215-439 µm 2 (mean area = 303 ± 93 µm 2 ). All of this correlated well with the rounded morphologies and nuclei, [28][29][30] and typical size (<20 µm in diameter; expected area around 314 µm 2 ) 31 reported for this cell line. Moreover, observation of the nuclei of the control cells mapped (shown by the concentrated regions of Zn), 32 suggested that the wide variation between their areas (ESI, Table S1 †) could be explained by their different stages of the cell cycle.…”
Section: Time-dependent Localisation Of Complexes Carrying Various Halogen Ligands In Cancer Cellssupporting
confidence: 84%
“…S2-4 †) also exhibited clear cell outlines with rounded shapes (mean roundness factor, RF: 0.77 ± 0.14; where RF = 1 implies perfect circularity), large cell nuclei, and overall area ranged between 215-439 µm 2 (mean area = 303 ± 93 µm 2 ). All of this correlated well with the rounded morphologies and nuclei, [28][29][30] and typical size (<20 µm in diameter; expected area around 314 µm 2 ) 31 reported for this cell line. Moreover, observation of the nuclei of the control cells mapped (shown by the concentrated regions of Zn), 32 suggested that the wide variation between their areas (ESI, Table S1 †) could be explained by their different stages of the cell cycle.…”
Section: Time-dependent Localisation Of Complexes Carrying Various Halogen Ligands In Cancer Cellssupporting
confidence: 84%
“…This work is the first to show that benzoxaboroles may serve as potent and efficacious anticancer agents. Although there are existing reports commenting on their anticancer activity, the reported potency at cellular level was not ideal and in vivo efficacy was not reported . However, the intracellular target of our benzxoaboroles remains to be elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…Although there are existing reports commenting on their anticancer activity, the reported potency at cellular level was not ideal and in vivo efficacy was not reported. 30 However, the intracellular target of our benzxoaboroles remains to be elucidated. They were demonstrated to effectively induce cancer cell apoptosis through the caspase 3/9 and PARP pathways and inhibited colony formation.…”
Section: Colony Formation Was Inhibited By Compound 103mentioning
confidence: 99%
“…Recently, it was found that 2-fluoro-6-formylphenylboronic acid and 3-morpholino-5-fluorobenzoxaborole exhibit strong cell cycle arrest induction in G2/M associated with caspase-3 activation in an A2780 ovarian cancer cell line [ 87 ].…”
Section: Antimicrobial Activitymentioning
confidence: 99%